Mini shopaholic a novel - Kinsella, Sophie (New York Dial Press, 2010)
Nothing comes between Becky Brandon (nee Bloomwood) and her bargains. Neither act of God nor budget crunch can shatter her dreams of wall-to-wall Prada. Every milestone in her well-shopped life (travel, long-lost sister, marriage, pregnancy) inspires new vistas to explore in the name of retail therapy. But now Becky faces her greatest little challenge yet: her two-year-old daughter, Minnie.
96344
Keywords: Bloomwood, Becky (Fictitious character); Mothers and daughters; Shopping; London (England); Christmas stories; Humorous fiction; Chick lit